The Participation of Pediatric Dentists in Oral Health Promotion and Education in Serbia - Kilibarda Biljana; Vuković Ana; Marković Evgenija; Perić Tamara; Petrović Bojan; Cakarević Vladimir; Matijević Stevo; Marković Dejan (Slovenian Journal of Public Health, 2023)
To identify the involvement of Serbian paediatric dentists in oral health promotion and education, and to propose further actions for the improvement of these activities.